Revisiting the musculocutaneous external oblique flap as a versatile alternative in large thoracic wall defects - David Matera; Richard Huynh; Terrance Hanley; Amir B. Behnam (Surgical Case Reports, 2019)
Abstract Background The external oblique myocutaneous flap has been previously described for reconstruction of chest-thoracic wall defects smaller than 400–500 cm2. However, it is utilized less often than workhorse flaps such as the omental, pectoralis, rectus abdominis, and latissimus dorsi myocutaneous flaps as many plastic surgeons are not aware that the flap can cover larger areas than previously documented. Case presentation We report a 57-year-old female tobacco user who underwent a resection of a grade 3 breast angiosarcoma resulting in a high left chest wall soft tissue defect approximating 900 cm2. The patient underwent an external oblique myocutaneous pedicle flap reconstruction of the defect, most notably in anticipation of postoperative adjuvant radiation therapy. No gross flap complications and or patient impairment were noted. Thirteen months status post flap reconstruction, the patient underwent an aortic valve replacement requiring re-elevation of the same flap for exposure. The flap demonstrated excellent viability during the procedure and postoperatively. Conclusion The pedicled external oblique myocutaneous flap should be considered when reconstructing larger high chest wall defects when other more common flaps used in chest reconstruction may not be indicated. The external oblique myocutaneous flap is an excellent tool in the armamentarium of any reconstructive surgeon; it is a straightforward and versatile flap that can be safely and reliably used in durable reconstruction of defects of the chest wall and covers defects larger than previously described in the literature.